Annual Review of Nursing Education : Clinical Nursing Education. - Oermann, Marilyn H. (Springer Pub. Co., 2007)
Addresses various trends, developments, and innovations in nursing education. This book provides information and ideas that educators and administrators can use in their nursing programs. It takes a look at such intriguing topics as innovations in clinical teaching and evaluation, partnerships for clinical teaching, and selecting clinical sites.